The severe abdominal effusion in a camel - Yılmaz Koç; Fahrettin Alkan; Alparslan Coşkun (Eurasian Journal of Veterinary Sciences)
In this case report was presented a 15 years old male dromedary camel with severe abdominal effusion. The exploratory laparotomy was performed through the left paralumbar lossae. The copious abdominal fluid at se-rosanguineous appearance with moderate inflammation was drained from abdominal cavity. The approximately 250300 liters fluid and 5.5-6 kg necrotic free fibrin masses were removed from abdominal cavity. An underlying gross lesion was not identified during abdominal exploratory surgery. The camel died 15 days after surgery.